(untitled) (Annals of Medical Research, 2021)
Aim: The impact of preoperative anemia in coronary artery bypass surgery (CABG) remains controversial and mostly associated with worse outcomes. Also, relationship between anemia and new on-set Atrial Fibrillation (NOAF) is still uncertain in patients who underwent CABG. This study aimed to investigate the anemia whether a risk factor of NOAF in patients who underwent isolated CABG.Material and Methods: Between March 2007 - December 2017 data of patients who underwent isolated CABG were retrospectively examined and 2027 patients included in study. Anemia was defined as hemoglobin level 13 g/dl for men and 12 g/dl for women. Patients were grouped as non-AF (n=1772) and AF (n=255) according to development of NOAF after CABG or not. Multivariate logistic regression analysis was performed to determine AF risk factors.Results:Overall anemia incidence of this study was 25.8% (n= 522). Also, anemia was observed in 17.4% of males and 52.2% of females. The incidence of anemia was similar in both groups; AF group 29% (n=74), non-AF group 25.3% (n=448) (p = 0.202). The mean hemoglobin and mean hematocrit level of AF and non-AF groups were similar (p=0.749, p=0.954 respectively) and 13.88 ± 1.77 g/dl, 13.84±1.63 g/dl and 41.13±5.48 %, 41.15±4.97 % respectively. Multivariate logistic regression analysis revealed that the parameters of mean hemoglobin, mean hematocrit and preoperative anemia were not NOAF risk factors after CABG. The parameters of carotid artery disease (OR=1.996), low LVEF (OR=1.429), BUN (OR=1.019), Euroscore (OR=1.151), need of inotrop (OR=2.270), mean perfusion time (OR=1.008), mean crosclamp time (OR=1.007) and mean ventilation time (OR=1.030) were independent risk factors of NOAF after CABG. Postoperative early mortality of groups were similar (p=0.299).Conclusion: Preoperative anemia was not a risk factor of NOAF in post-CABG patients. In addition, the mortality-enhancing effect of preoperative anemia was not detected in AF patients.